The effect of di (n-butyl) phthalate (dbp) on the reproductive function of the adult male Japanese quails (Coturnix coturnix japonica) - Madekurozwa, Mary-Catherine. (2026)
Thesis (PhD (Anatomy and Physiology))--University of Pretoria, 2015.